In-house reagent for creatinine in Synchron CX-3 delta - P Choosongsang; A Bodhikul; P Ruengrairatanaroj; B Wilirat; P Choosongsang (Journal of Health Science and Medical Research (JHSMR), 2008)
An in-house reagent for the determination of creatinine inserum was prepared and evaluated using the Beckman Synchron CX-3 delta automatic analyzer. The reagent was compared with the commercially available reagent. This study compared the in-house and the commercial reagent in 220 specimens. The accuracy assessed by the average recovery was 105.6% and 101.6% respectively. The precision was evaluated by analyzing three levels of the chemistry control serum. It was found that the within-run and between-run coefficients of variation (%CV) of the in-house reagent were 2.89% to 3.33% and 1.58% to 5.00%, whereas those of the commercial were 0.00% to 1.30% and 1.43% to 5.00% respectively. The inhouse and commercial reagent showed the same detection limit and linearity of 0.1 mg/dL and 25 mg/dL, respectively. The correlation (r) of creatinine was 0.997 (y=0.9919x+0.0557) with no significant difference found (p>0.05). In conclusion, the in-house reagent showed satisfactory results for the determination of creatinine. It was found to be as good as the commercial reagent. Therefore, this in-house reagent for the determination of creatinine is applicable for routine use in clinical chemistry labs. Moreover, the cost of this reagent is about fifty times lower than that of the commercial reagent.